2014
DOI: 10.1063/1.4891714
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of single crystal elastic constants for yttria partially stabilised zirconia from powder diffraction data

Abstract: Articles you may be interested inGrain and the concomitant ferroelectric domain size dependent physical properties of Ba0.85Ca0.15Zr0.1Ti0.9O3 ceramics fabricated using powders derived from oxalate precursor route Yttria Stabilised Zirconia (YSZ) is a tough, phase-transforming ceramic that finds use in a wide range of commercial applications from dental prostheses to thermal barrier coatings. Micromechanical modelling of phase transformation can deliver reliable predictions in terms of the influence of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A distinct variation in Young's modulus is also observed within the first 10 μm of the interface, with a reduced stiffness found in four measurements closest to the interface. Monoclinic YPSZ is known to have a smaller bulk elastic modulus than tetragonal YPSZ, and this may be the origin of this behaviour [49]. The impact of elemental diffusion may also be influencing the near-interface YPSZ state and mechanical response, with diffusion of silicon being observed up to 2 − 3 μm into the YPSZ.…”
Section: Compendium Of Mechanical Microscopy Of the Ypsz-porcelain Inmentioning
confidence: 99%
“…A distinct variation in Young's modulus is also observed within the first 10 μm of the interface, with a reduced stiffness found in four measurements closest to the interface. Monoclinic YPSZ is known to have a smaller bulk elastic modulus than tetragonal YPSZ, and this may be the origin of this behaviour [49]. The impact of elemental diffusion may also be influencing the near-interface YPSZ state and mechanical response, with diffusion of silicon being observed up to 2 − 3 μm into the YPSZ.…”
Section: Compendium Of Mechanical Microscopy Of the Ypsz-porcelain Inmentioning
confidence: 99%
“…The singlecrystal elastic constants of any polycrystalline material may then be determined by an inversion of the usual calculations applied in the residual stress analysis and fitting by a 2 -minimization technique. The feasibility of such an ISSN 1600-5767 approach was demonstrated by Hauk & Kockelmann (1979) and later applied by various authors (Gnä upel-Herold et al, 1998;Kisi & Howard, 1998;Singh et al, 1998;Howard & Kisi, 1999;Matthies et al, 2001;Fré our et al, 2005;Stebner et al, 2013;Lunt et al, 2014;Kim et al, 2016) for alloys and ceramics by diffraction under tensile stress or compression. This technique is of particular relevance for any engineering material which cannot be obtained as a single crystal, especially multiphase or highly twinned materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have shown the structural and mechanical properties of 6-15 mol% doped yttria-stabilized zirconia and they are mechanically stable. An understanding of the diffusion of oxygen vacancies with migration energy barriers is also essential for technological applications [20][21][22][23].…”
Section: Mechanical Propertiesmentioning
confidence: 99%